Conformational Plasticity in Broadly Neutralizing HIV-1 Antibodies Triggers Polyreactivity - Julie Prigent; Annaëlle Jarossay; Cyril Planchais; Caroline Eden; Jérémy Dufloo; Ayrin Kök; Valérie Lorin; Oxana Vratskikh; Thérèse Couderc; Timothée Bruel; Olivier Schwartz; Michael S. Seaman; et al. (Cell Reports, 2018)
Human high-affinity antibodies to pathogens often recognize unrelated ligands. The molecular origin and the role of this polyreactivity are largely unknown. Here, we report that HIV-1 broadly neutralizing antibodies (bNAbs) are frequently polyreactive, cross-reacting with non-HIV-1 molecules, including self-antigens. Mutating bNAb genes to increase HIV-1 binding and neutralization also results in de novo polyreactivity. Unliganded paratopes of polyreactive bNAbs with improved HIV-1 neutralization exhibit a conformational flexibility, which contributes to enhanced affinity of bNAbs to various HIV-1 envelope glycoproteins and non-HIV antigens. Binding adaptation of polyreactive bNAbs to the divergent ligands mainly involves hydrophophic interactions. Plasticity of bNAbs’ paratopes may, therefore, facilitate accommodating divergent viral variants, but it simultaneously triggers promiscuous binding to non-HIV-1 antigens. Thus, a certain level of polyreactivity can be a mark of adaptable antibodies displaying optimal pathogens’ recognition.